VentiVet: Development of a graphical interface in MATLAB for small animal mechanical ventilators - de Lima, Amanda Fila; Andrade, Brayan Agio de Miranda; Pês, Beatriz do Santos; Tefili, Diego; Hara, Marcos Santos (Seven Editora, 2024)
A pulmonary ventilator is a respiratory support equipment for surgical or clinical procedures, such as those that require general anesthesia, for example. The construction of this type of equipment can involve knowledge of several areas, such as closed-loop control systems, software development, sensing, and communication protocols. This paper presents the development of a pulmonary ventilator for small animals and the implementation of a graphical interface for monitoring and parameter adjustment. The veterinary ventilator built has an Arduino Uno microcontrolled platform, a pressure sensor and ball valves with proportional flow control, built with servo motors, performing the functions of expiratory and inspiratory valve, through a proportional control algorithm implemented in firmware. In addition, the graphical interface is developed in MATLAB, enabling parameter adjustments and visualization of ventilatory data and alarms, which are essential for the safe operation of the ventilator. Unlike other projects presented in the literature, the prototype uses compressed air and not manual, with the implementation of the PCV ventilation mode - ventilation with controlled pressure, in controlled cycles. The prototype also has a dynamic interface with a display of the measured pressure history on a real-time graph, as well as controls and adjustments. DOI:https://doi.org/10.56238/sevened2023.006-159